Acinetobacter gandensis sp. nov. isolated from horse and cattle - Smet, Annemieke; Cools, Piet; Krizova, Lenka; Maixnerova, Martina; Sedo, Ondrej; Haesebrouck, Freddy; Kempf, Marie; Nemec, Alexandr; Vaneechoutte, Mario (International journal of systematic and evolutionary microbiology, 2014)
We previously reported the presence of an OXA-23 carbapenemase in an undescribed species of the genus Acinetobacter isolated from horse dung at the Faculty of Veterinary Medicine, Ghent University, Belgium. Here we include six strains to corroborate the delineation of this taxon by phenotypic characterization, DNA-DNA hybridization, 16S rRNA gene and rpoB sequence analysis, % G+C determination, MALDI-TOF MS and fatty acid analysis. The nearly complete 16S rRNA gene sequence of strain UG 60467(T) showed the highest similarities with those of the type strains of Acinetobacter bouvetii (98.4 %), Acinetobacter haemolyticus (97.7 %), and Acinetobacter schindleri (97.2 %). The partial rpoB sequence of strain UG 60467(T) showed the highest similarities with 'Acinetobacter bohemicus' ANC 3994 (88.6 %), A. bouvetii NIPH 2281 (88.6 %) and A. schindleri CIP 107287T (87.3 %). Whole-cell MALDI-TOF MS analyses supported the distinctness of the group at the protein level. The predominant fatty acids of strain UG 60467(T) were C12 : 0 3-OH, C12 : 0, C16 : 0, C18 : 1ω9c and summed feature 3 (C16 : 1ω7c and/or iso-C15 : 0 2-OH). Strains UG 60467(T) and UG 60716 showed a DNA-DNA relatedness of 84 % with each other and a DNA-DNA relatedness with A. schindleri LMG 19576(T) of 17 % and 20 %, respectively. The DNA G+C content of strain UG 60467(T) was 39.6 mol%. The name Acinetobacter gandensis sp. nov. is proposed for the novel taxon. The type strain is UG 60467(T) ( = ANC 4275(T) = LMG 27960(T) = DSM 28097(T)).
Keywords: zastoupení bazí; Cattle; Feces; Belgium; fylogeneze; techniky typizace bakterií; RNA, Ribosomal, 16S; skot; mastné kyseliny; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Nucleic Acid Hybridization; molekulární sekvence - údaje; Fatty Acids; hybridizace nukleových kyselin; Acinetobacter; DNA, Bacterial; DNA bakterií; Animals; Genes, Bacterial; zvířata; Base Composition; Belgie; Horses; koně; RNA ribozomální 16S; Bacterial Typing Techniques; Molecular Sequence Data; feces; bakteriální geny